Structure Determination of Chitosan-Stabilized Pt and Pd Based Bimetallic Nanoparticles by X-Ray Photoelectron Spectroscopy and Transmission Electron Microscopy - Mohd Ridzuan, Nordin; Shafii, Salimah; Wu, Lihua; Liew, Kong Yong; Li, Jinlin (Elsevier, 2012)
Chitosan (CTS)-stabilized bimetallic nanoparticles were prepared at room temperature (rt.) in aqueous solution. Palladium (Pd) and platinum (Pt) were selected as the first metals while iron (Fe) and nickel (Ni) functioned as the second metals. In order to obtain the noble metal core-transition metal shell structures, bimetallic nanoparticles were prepared in a two-step process: the preparation of mono noble metallic (Pd or Pt) nanoparticles and the deposition of transition metals (Fe or Ni) on the surface of the monometallic nanoparticles. The structures of the nanoparticles were studied using X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM). The XPS results show that Pd and Pt exist mainly in zero valences. The presence of Fe and Ni in the bimetallic nanoparticles affects the binding energy of Pd and Pt. Moreover, the studies of O 1s spectra indicate the presence of Fe or Ni shells. The analyses of TEM micrographs give the particle size and size distributions while the high-resolution TEM (HRTEM) micrographs show the existence of noble metal core lattices. The results confirm the formation of noble metal core-transition metal shell structures